“Gestión de la calidad en los procesos de la hacienda sarita de la empresa constructora arregui davila s.a.” - Pino Campuzano, Kevin Paul (2022)
The quality management in the processes of a company are relevant at the time of decision making, this allows to have updated and organized information, the case study entitled "QUALITY MANAGEMENT IN THE PROCESSES OF THE HACIENDA SARITA OF THE CONSTRUCTION COMPANY ARREGUI DAVILA SA. "Due to the problems generated by the non-existence of a management system, as part of this, there is the lack of updating of the personnel who keep the data in a disorganized way, which has allowed the objective of analyzing the quality management in the processes of the Hacienda, which was possible thanks to the implementation of the interview technique, which led to obtain relevant data about the current situation of the administrative part of the company, The results obtained showed that they do not have their own system and that until now the most practical way is to keep the information manually, in addition the administrators pretend that nothing happens, no damage is evaluated and no inconsistencies are reported, reaching the conclusion that it is urgent to implement an updated system that governs the functions in a correct way so as not to cause discomfort in any of the areas that compose it. The quality management systems not only seek to improve the activities within the administrative area, but this must be organized because otherwise it can generate problems at the level of productivity, not having the raw materials or materials needed to perform the work within the farm.